Dietary flaxseed oil improved western-type diet-induced atherosclerosis in apolipoprotein-E knockout mice - Hao Han; Fubin Qiu; Haifeng Zhao; Haiying Tang; Xiuhua Li; Dongxing Shi (Journal of Functional Foods, 2018)
Flaxseed oil is a rich source of n-3 fatty acid alpha-linolenic acid which has been identified as having significant cardioprotective effects. The objective of this study was to investigate the effect of partial replacement of lard with flaxseed oil on atherosclerosis and investigate the underlying mechanisms. Apolipoprotein-E knockout mice were given a normal chow diet, a lard based western-type high-fat diet (WTD), or a WTD with partial replacement of lard with 10% flaxseed oil (w/w) for 16 weeks, respectively. Results demonstrated that partial replacing of lard with flaxseed oil significantly ameliorated atherosclerosis, as well as improved lipid abnormalities, oxidative stress, and inflammation. These data were associated with modification effects on expression of genes involved in lipid metabolism (SREBP-2, HMGCR, SREBP-1c, and ACC), oxidative stress (NADPH oxidase), and inflammation (TNF-α, IL-6, MCP-1, and VCAM-1). Our data providing evidence that flaxseed oil could be a promising functional food in cardiovascular health promotion.